1992
DOI: 10.1021/jm00102a015
|View full text |Cite
|
Sign up to set email alerts
|

DL-Tetrazol-5-ylglycine, a highly potent NMDA agonist: its synthesis and NMDA receptor efficacy

Abstract: At physiological pH, the spatial arrangement of the three charges of DL-tetrazol-5-ylglycine (5) could be viewed as similar to those found in certain conformations of the two excitatory amino acids (EAAs)--aspartic and glutamic acids. Given significant binding to one or more EAA receptors, 5 would offer unique modeling and perhaps biological opportunities. We have previously shown it to be the most potent NMDA agonist known, with a unique and marked in vitro neutrotoxicity at depolarizing concentrations. Now w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…19,20 In the present work reaction of compound 7 with sodium azide in presence of triethylamine hydrochloride gave the final compound 9 in fairly low yield (48%) and also time required for the reaction was 52 h. Therefore, we designed a facile new scheme with improvement in the yield (scheme 2).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…19,20 In the present work reaction of compound 7 with sodium azide in presence of triethylamine hydrochloride gave the final compound 9 in fairly low yield (48%) and also time required for the reaction was 52 h. Therefore, we designed a facile new scheme with improvement in the yield (scheme 2).…”
Section: Resultsmentioning
confidence: 89%
“…150-151 • C). (13): 1 H NMR (300 MHz, DMSO-d 6 )δ 4.48 (s, 2H, CH 2 ), 7.00-7.84 (m, 23H, ArH); 13 C NMR (300 MHz,64.6,111.9,127.4,127.9,128.2,128.4,129.0,129.2,129.4,129.5,127.4,135.1,135.4,136,136.8,141.0,144.0,151.4 (21), 271 (28), 246 (12), 244 (19), 153 (100), 77 (67); Anal. Calcd.…”
Section: 3cmentioning
confidence: 99%
“…Data collection: APEX2 (Bruker, 2005); cell refinement: SAINT (Bruker, 2005); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: PLATON (Spek, 2009) and ORTEP-3 for Windows (Farrugia, 1997); software used to prepare material for publication: publCIF (Westrip, 2010). Tetrazoles derivatives are an important class of compounds, which can be used in the fields of bioorganic and medicinal chemistry as antibacterials, anti-cancer, heart disease, neurodegenerative disease, and antifungal activity (Smissman et al,1976;McGuire et al, 1990;Lunn et al, 1992;Itoh et al, 1995;Upadhayaya et al, 2004;Wu et al, 2008;Rostom et al, 2009. The tetrazole moiety has long been established as a bioisostere of a carboxyl unit (Burger, 1991). A major advantage of tetrazoles over carboxylic acids is that they are resistant to many biological metabolic degradation pathways (Singh et al, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…For the biological activity and medicinal properties of tetrazole derivatives, see : Smissman et al (1976); McGuire et al (1990); Lunn et al (1992); Itoh et al (1995); Upadhayaya et al (2004); Wu et al (2008); Rostom et al (2009);Burger (1991); Singh et al (1980). For the synthetic procedure, see: Adams & Langley (1941a,b).…”
Section: Related Literaturementioning
confidence: 99%
“…However, TZG can induce tonic-clonic seizures and exhibits a very steep dose response for seizure induction (Schoepp et al, 1991;Lunn et al, 1992). Consitent with the study of Inada et al (2007), Schoepp et al (1991) found that a TZG dose of 0.75 mg/kg did not induce seizures in any mice tested.…”
Section: Introductionmentioning
confidence: 93%